Variable-Elliptic-Vortex Method for Incompressible Flow Simulation (Journal of Computational Mathematics, 2018)
A variable-elliptic-vortex method, which is a generalization of the elliptic-vortex method proposed by the author in [1], is presented for the numerical simulation of incompressible flows. The most attractive feature of the new method is that the numerical vortex blobs used in this model like actual vortex blobs can be translated, rotated and deformed in elliptic shape. The new method provides a more reasonable and more accurate approach for flow simulation than the fixed-vortex methods. Numerical examples are presented to demonstrate the performance of the new method.